Herbisida Parakuat dalam Lahan Gambut: II. Pengaruhnya terhadap Pertumbuhan dan Hasil Kedelai - Erni Martani; Bambang Hendro Sunarminto; Agus Supriyo; Sebastian Margino (Universitas Gadjah Mada, 2001)
Utilization of peat soil for agriculture faces several constraints, such as low soil fertility and pH value. No-tillage agricultural system in peat land needs application of herbicides, for example herbicides with paraquat as active agent. This research was conducted to study the influence of paraquat on the growth and yield of soybean in peat. Peat soil from Central Kalimantan Province was obtained for this study. Due to the requirement of the plant, the soil was treated with lime and NPK-fertilizers. The results showed that paraquat significantly inhibited vegetative growth and decreased soybean production. These phenomena were found in early and advanced decomposed peat soil. Enhancement of vegetative growth and yield were detected when peat was treated with lime and or fertilizers. Liming treatment also supported the formation of root nodules. Inspite of increasing the growth of soybean, lime and fertilizers addition in peat was able to neutralize the negative effect of paraquat on the growth and yield of soybean. The best growth and yield of soybean were found in early decomposed peat soil, i.e. fibric peat soil.